Temporal dynamics of justice climate and team innovation - Tripathi, Neha; Sangar, Sukanya (Frontiers in Psychology, 2023)
Team innovation – exploration and exploitation of useful and novel ideas by a team has been a topic of great importance for organizations in today’s dynamic, complex, and competitive environment. Grounded in the social contagion theory of justice (Degoey, 2000), we theorize a justice-to-innovation processual model based on within-team justice climate occurrences that change across time. We posit that collective and shared justice perceptions of team members construct dynamically based on justice-related work events. Within teams, state justice climate level and strength (represented by the Mean and the low-SD scores of individual team members in the moment or in an episode) are important precursors of team innovation. The proposed theoretical model explicates an emotional contagion process arguing that positive and negative team affective states mediate the relationship between state justice climate and team innovation. Positive/negative team affective states result in collective actions and team interactions that foster/hinder team innovation. The present article significantly contributes to development of the dynamical models of justice and innovation for teams where most research is confined to static models of justice climate.